Safety and efficacy of high‐dose cytarabine MEAM therapy and other treatments for auto‐peripheral blood stem cell transplantation: A retrospective comparative study. Issue 1 (22nd May 2022) - Yui, Shunsuke; Wakita, Satoshi; Nagata, Yasunobu; Kuribayashi, Yasuko; Asayama, Toshio; Fujiwara, Yusuke; Sakaguchi, Masahiro; Yamanaka, Satoshi; Marumo, Atsushi; Omori, Ikuko; Kinoshita, Ryosuke; Onai, Daishi; et al.
Abstract: Aim: The MEAM regimen consisting of ranimustine (MCNU), etoposide (ETP), cytarabine (Ara‐C), and melphalan (MEL) is widely used before auto‐peripheral blood stem cell transplantation (auto‐PBSCT) for malignant lymphoma in Japan. The MEAM regimen generally consists of 200–400 mg/m 2 for 4 days, but we decided to increase the dosage of Ara‐C from the standard to 2 g/m 2 for 2 days with the aim of increasing drug transferability to the central nervous system. We evaluate the safety and therapeutic efficacy of high‐dose Ara‐C MEAM therapy. Methods: The high‐dose Ara‐C MEAM protocol consisted of MCNU 300 mg/m 2 on day –7, ETP 200 mg/m 2 on days –6, –5, –4, –3 and Ara‐C 2 g/m 2 on day –4 –3, and MEL 140 mg/m 2 on day –2. We retrospectively analyzed 37 cases of malignant lymphoma at our institution between May 2014 and July 2020. Results: All patients got engraftment and there were no cases of treatment‐related mortality. In all cases, the 3‐year overall survival (OS) and progression‐free survival (PFS) after transplantation were 80.6% and 65.7%, respectively. Twenty‐one cases of diffuse large B‐cell lymphoma recurrence, for which there is proven usefulness of auto‐PBSCT, showed good results after transplantation, with the 3‐year OS and PFS after transplantation being 100% and 74.3%, respectively. Conclusion: The safety and efficacy of high‐dose Ara‐C MEAM therapy were demonstrated, but the expected therapeutic effect on central nervous system lesions could not be fully evaluated owing to the small number of cases. Abstract : We retrospectively analyzed malignant lymphoma in patients who underwent auto‐peripheral blood stem cell transplantation, with high‐dose cytarabine MEAM therapy as the conditioning regimen. In all cases, the 3‐year overall survival after transplantation was 80.6% and the 3‐year progression‐free survival after transplantation was 65.7%. There were no cases of treatment‐related mortality with this therapy, and this one tended to be more effective than ICE and BU/CY/VP‐16 therapies.